Perancangan Buku Cerita Pengetahuan Anak dengan Tema Sains - Nurlita Priyandini; Rendy Iswanto (Jurnal Vicidi, 2017)
The problems of education in Indonesia until today to make an impact to future generations. The learning process should be able to make children aware of what is learned. Besides the support of the parents is necessary for children. It would be more effective if given correctly learning starts from the age of development. The main objective of this study was to find out how to create a medium of learning for children aged development that is easily understood and applied with parents. This study uses qualitative research methods (interviews), observation and study of literature. The results of the research to produce a solution in the form of a story book knowledge themed science for ages 9-11 years.